MBTPS1 regulates proliferation of colorectal cancer primarily through its action on sterol regulatory element-binding proteins - Hartal-Benishay, Liat H.; Saadi, Esraa; Toubiana, Shir; Shaked, Lior; Lalzar, Maya; Abu Hatoum, Ossama; Tal, Sharon; Selig, Sara; Barki-Harrington, Liza (Frontiers in Oncology, 2022)
Among the main metabolic pathways implicated in cancer cell proliferation are those of cholesterol and fatty acid synthesis, both of which are tightly regulated by sterol regulatory element-binding proteins (SREBPs). SREBPs are activated through specific cleavage by membrane bound transcription factor protease 1 (MBTPS1), a serine protease that cleaves additional substrates (ATF6, BDNF, CREBs and somatostatin), some of which are also implicated in cell proliferation. The goal of this study was to determine whether MBTPS1 may serve as a master regulator in proliferation of colorectal cancer (CRC). Tumors from CRC patients showed variable levels of MBTPS1 mRNA, which were in positive correlation with the transcript levels of SREBFs and ATF6, and in reverse correlation with BDNF levels. Chemical inhibition of MBTPS1 activity in two CRC-derived cell lines resulted in a marked decrease in the levels of SREBFs, but not of its other substrates and a marked decrease in cell proliferation, which suggested that MBTPS1 activity is critical for proliferation of these cells. In accordance, CRISPR/Cas9 targeted knockout (KO) of the MBTPS1 gene resulted in the survival of only a single clone that presented a phenotype of severely attenuated proliferation and marked downregulation of several energy metabolism pathways. We further showed that survival of the MBTPS1 KO clone was dependent upon significant upregulation of the type-1 interferon pathway, the inhibition of which halted proliferation entirely. Finally, rescue of the MBTPS1 KO cells, resulted in partial restoration of MBTPS1 levels, which was in accordance with partial recovery in proliferation and in SREBF levels. These finding suggest that MBTPS1 plays a critical role in regulating colon cancer proliferation primarily through SREBP-associated lipid metabolism, and as such may serve as a possible therapeutic target in CRC.